PATRONAGE OF LEARNING AND THE ARTS IN MEDIEVAL KASHMIR: SULTAN ZAIN-UL-ABIDIN AND THE CULTURAL RENAISSANCE OF THE VALLEY - Shabir Ahmad Lone (PT. Radja Intercontinental Publishing, 2025)
Sultan Zain-ul-Abidin (1420–1470 A.D.), popularly known as Budshah, is regarded as the most enlightened ruler of the Kashmir Sultanate. His long reign marked a decisive phase in the political stability, cultural florescence, and socio-economic development of medieval Kashmir. This study examines the multidimensional contributions of Sultan Zain-ul-Abidin, focusing on his administrative efficiency, public works, educational reforms, patronage of arts and crafts, and policy of religious tolerance. Drawing upon Persian chronicles such as Rajatarangini Dvitiya by Jonaraja and Rajatarangini Tritiya by Srivara, the paper situates his governance within both historical documentation and popular memory. The Sultan adopted a welfare-oriented approach to governance by initiating extensive public works, including irrigation canals, bridges across the Jhelum River, artificial islands in Dal Lake, hospitals, dispensaries, caravanserais, and planned urban centres like Zainapura. These measures significantly strengthened agriculture, trade, and public welfare. His commitment to education was equally remarkable; he established schools, colleges, hostels, and a royal library, sponsored translations of classical Sanskrit texts into Persian, and encouraged learning across social groups. Under his patronage, Kashmir emerged as a major centre of scholarship, attracting scholars, poets, and intellectuals from Central Asia and the Indian subcontinent. Zain-ul-Abidin also played a pivotal role in reviving and institutionalising arts and crafts such as carpet weaving, shawl making, papier-machie, wood carving, metalwork, papermaking, and bookbinding, laying the foundation of Kashmir’s renowned handicraft tradition. His religious policy, marked by tolerance and inclusivity, abolished discriminatory practices against non-Muslims and fostered interfaith harmony, contributing to the evolution of Kashmiriyat. Despite facing natural calamities and internal political challenges, his reign remained a model of benevolent and just kingship, the legacy of which continues to inspire Kashmiri society.